Effect of GCG, ROA and DER to Predict Financial Distress on Property and Real Estate Companies in BEI 2014-2018 period - Silvia Silvia; Linda Linda; Teddy Nugroho; Jesica Jesica; Faathir Nurul Yaasiin (Jurnal Mantik, 2020)
This paper aims to predict financial distress as seen from the factors of GCG, ROA and DER. This research was conducted in the property and real estate sector, amounting to 52 companies with a sample of 27 companies. The data analysis tool used was multiple discriminant analysis. The results of this data test meet the four requirements of the classical assumption test. The GCG variable in this study uses an independent commissioner proxy and to predict financial distress uses the Altman Z Score formula. The conclusion of this research is that partially GCG (independent commissioner) is notable to distinguish between bankrupt, gray and healthy companies, while partially ROA and DER able to distinguish between bankrupt, gray and healthy companies